On the Creep Fatigue Behavior of Metal Matrix Composites. (2015) - Barbera, D.; Chen, H.F.; Liu, Y.H.
Abstract: The mechanical behaviour of Metal Matrix Composites (MMCs) subjected to a high temperature and cyclic load condition is difficult to understand. The significantly differing coefficients of thermal expansion between ceramic and metal give rise to micro thermal stresses. Their performance under varying load and high temperature is complex and inconsistent, where fatigue and creep damages become the main failures of MMCs. To improve current understanding of the relationship between creep fatigue interaction of MMCs, the history of thermal and mechanical loading, and the creep dwell period, a highly accurate but robust direct simulation technique on the basis of the Linear Matching Method (LMM) framework has been proposed in this paper, and been applied to model the fatigue and creep behaviour of MMCs. A homogenised FE model is considered in all analyses, which consist of continuous silicon carbide fibres embedded in a square 2024T3 aluminium alloy matrix array. Various factors that affect creep and fatigue behaviours of composites are analysed and discussed, including effects of the applied load level, dwell period and temperature on the MMC's performance. The effects of reversed plasticity on stress relaxation and creep deformation of MMC are investigated, and the behaviours of cyclically enhanced creep and elastic follow-up are presented. The applicability and accuracy of the proposed direct method has also been verified by the detailed step-by-step analysis via Abaqus.